Inobservancia del numeral dos del artículo setenta y seis de la constitución de la república del ecuador, en relación con el principio de presunción de inocencia del infractor en el juzgamiento de las infracciones contempladas en la ley contra la violencia a la mujer y a la familia - Vargas Diaz, Ligia Elena (2014)
In the country it exists a constitutional and legal mark that explicitly protects people that are victims of violence intra family, mainly to women, girls, children, adolescents, inability and people of the third age. The Woman's Police stations and the Family together with the setting in validity of the Law against the Violence to the Woman and the Family, they opened an access door to the women to the administration of justice for infractions that had not been considered as such. In the year 2005 you development and it published the regulation of application of the Law against the Violence to the Woman and the Family, where it is framed all the normative ones legal for the respective process, inside which is not considered the existent principle in Art. 72 numeral 2 of the Constitution of the Republic that it points out that "In all process in the one that rights and obligations of any order are determined, he/she will make sure the right to the due process that will include the basic following guarantees: .2. One shows off the innocence of all person and it will be treated as such, while their responsibility firm mediating resolution is not declared or it sentences is finish. In spite of the conventions, declarations and agreements that are signed a true will it doesn't exist to maintain the perspective of the human rights and to take a fair process without violating the constituent rights of the citizens; since in the Woman's Police stations and the Family, they don't take in consideration all the necessary basics for a legitimate demand and to begin a fair process; without violating the human rights of any person although being held of the call help measure deprives from the freedom to the presumed offender without before to corroborate the information of the demand legitimate mediating tests presented by the accusatory part. Taking in consideration all the mentioned aspects, you can indicate that the existence of the Law against the Violence to the Woman and the Family has provoked a space of legislative respect, for the women and its families with the purpose of braking the aggression, even so it has been bad be seen when not respecting the constitutional rights of the presumed offenders reason why it is necessary to reinforce the legal text harmonizing him with other related norms, especially in what refers to the presumption of the defendant's innocence.